2022
DOI: 10.2224/sbp.11319
|View full text |Cite
|
Sign up to set email alerts
|

Family-supportive supervisor behavior and employees' workplace deviant behavior: Moral disengagement as a mediator

Abstract: Workplace deviant behavior causes not only physical and mental harm to employees but also great losses to the enterprise where they are employed. Drawing on social cognitive theory, in this study we explored the mechanism of family-supportive supervisor behavior on employees' workplace deviant behavior. Analysis of data from 312 participants showed that family-supportive supervisor behavior negatively influenced employees' workplace deviant behavior, and that moral disengagement played a mediating role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Furthermore, personal life attribution would raise workers' organizational emotional attachment, improving job engagement and decreasing WDB ( Hypothesis 4 ). Relating to the body of knowledge, other scholars have also found that Employees' deviant behavior at work is negatively influenced by family supportive supervisor behavior, and moral disengagement was found to play a role in mediating the relationship between these two variables [ 132 ]. Scholars like Muse and Pichler [ 133 ], have also highlighted that supervisor support had negative effects on work-family conflict in both the same domain (work-interference-with-family) and the cross-domain (family-interference-with-work), as well as positive relationships with task and contextual performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, personal life attribution would raise workers' organizational emotional attachment, improving job engagement and decreasing WDB ( Hypothesis 4 ). Relating to the body of knowledge, other scholars have also found that Employees' deviant behavior at work is negatively influenced by family supportive supervisor behavior, and moral disengagement was found to play a role in mediating the relationship between these two variables [ 132 ]. Scholars like Muse and Pichler [ 133 ], have also highlighted that supervisor support had negative effects on work-family conflict in both the same domain (work-interference-with-family) and the cross-domain (family-interference-with-work), as well as positive relationships with task and contextual performance.…”
Section: Discussionmentioning
confidence: 99%
“…First, FSSB has been shown to directly enhance employee workplace habits; consequently, firms should strive hard to produce family-supportive supervisors [ 92 ]. On the one hand, firms must offer training and mentorship programs for managers for them to participate in FSSB, as also mulled by other scholars [ 4 , 132 ]. Leaders should be encouraged to assist workers with the information and technical guidance they need to address challenges at work and enhance their family's supportive management abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested intra-personal congruence between ILTs and characteristics recognized in an individual's current supervisor impact attitudinal and behavioral aspects of workplace engagement (Blomme et al ., 2015; Dunlop and Lee, 2004; Gok et al ., 2017; Kaishoven and Den Hartog, 2013; Kong et al ., 2020; Zhang et al ., 2022). ILT–supervisor alignment has been shown to impact performance, LMX, organizational citizenship behavior (OCB), work–family conflict and counter-productive work-behavior (CWB) (Biermeier-Hanson and Coyle, 2019; Epitropaki and Martin, 2005; Rupprecht et al ., 2016; Topakas, 2011).…”
Section: Theoretical Foundation and Hypothesesmentioning
confidence: 99%
“…Finally, studies have also found that ethical supervisor behavior (e.g. unethical leader behavior, family-supportive behavior) impacts employee's deviance in the workplace (Dunlop and Lee, 2004; Zhang et al ., 2022). Taken together, these studies provide sufficient evidence that intrapersonal congruence between a subordinate's ILT of an ethical leader and characteristics recognized in their current supervisor will be related to attitudinal and behavior aspects of workplace engagement.…”
Section: Theoretical Foundation and Hypothesesmentioning
confidence: 99%